5-Aza-2'-deoxycytidine may enhance the frequency of T regulatory cells from CD4+ naïve T cells isolated from the peripheral blood of patients with chronic HBV infection. (1st February 2021) - Fang, Yu; Yuan, Xiao-Dong; Liu, Hui-Hui; Xiang, Lin; Chen, La-Mei; Fan, Yu-Chen; Gao, Shuai; Wang, Kai
ABSTRACT: Objectives: Methylation pattern of gene modification is essential for the differentiation of T regulatory cells (Tregs) and 5-Aza-2ʹ-deoxycytidine is a common inhibitor of methylation. This study aimed to investigate the potential effects of Treg polarizing conditions and 5-Aza-2ʹ-deoxycytidine treatment in the differentiation of naïve T cells during chronic hepatitis B virus (HBV) infection. Methods: The frequency of Tregs in peripheral blood was determined by flow cytometry from patients with chronic hepatitis B (CHB) (n = 51), liver cirrhosis (LC) (n = 47), hepatocellular carcinoma (HCC) (n = 40) and healthy controls (HCs) (n = 17). Gene expression were detected by qRT-PCR and DNA methyltransferases (DNMT) Activity was also determined. Results: The frequency of Tregs and Foxp3 expression in peripheral blood from 5-Aza-2ʹ-deoxycytidine-treated groups were higher than that with acetic acid treatment as a control. Foxp3 mRNA and the frequency of Tregs derived from naïve CD4 + T cells from peripheral blood of patients with HCC or LC were more pronounced compared with HCs. 5-Aza-2ʹ-deoxycytidine may have induced a more pronounced upward trend of PD-1 expression in HBV patients. Conclusions: 5-Aza-2ʹ-deoxycytidine mediated demethylation has potential effects on enhancing the differentiation of naïve T cells to Tregs in chronic HBV infection.